Overview on the research of dictionaries in Chagatai language - Н.Н., Кaйрaнбaевa; З., Шaдкaм (Journal of Oriental Studies, 2019)
Abstract. The Chagatai language is the common literary language of the Turkic peoples of Central Asia from the first half of the 14th to the beginning of the 20th century. In order to understand the literary language of famous poets and writers of that time, dictionaries in the Chagatai language were compiled. The interest to the study of ancient Turkic dictionaries in the Chagatai language which is considered as a significant topic for Turkology started in the 19th century. The main purpose of the article is to provide complete information about the dictionaries of the Chagatai language based on the collected materials, create a predictable chronological classification of the research, consider and compare studies on dictionaries. The study used methods of comparative analysis, gathering information and classification. The main conclusions were deduced in the article and some suggestions for studying the dictionaries of the Chagatai dictionaries are given. Based on the key issues of the study, we came to conclusion that many of the Chagatai language dictionaries have not been fully explored yet, this topic has not been fully considered by Kazakh Turkologists, there were also found encountered some mistakes in the Chagatai language dictionaries. Key words: Chagatai language, dictionaries in Chagatai language, Alisher Navoi, medieval Turkic language.